Characterization of dengue type 2 new guinea C virus infection in c6/36, vero and MRC-5 cells. - Shafee, Norazizah; Abu Bakar, Sazaly (Academic Journals, 2011)
Dengue viruses have been shown to infect a wide variety of cell lines with different consequences. In this study, cellular responses to dengue virus type 2 New Guinea C strain (D2NGC) viral infection in mosquito gut (C6/36), African green monkey kidney (Vero) and human lung fibroblast (MRC-5) cells were investigated. Microscopic and immunostaining studies of infected cells showed different patterns of infection in each cell lines reflecting the different degrees of permissiveness to D2NGC infection. Using a terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL) staining method, we showed that D2NGC virus induced apoptosis in the three cell lines studied. However, the levels of apoptotic cells in each cell lines varied suggesting that programmed cell death is dependent on the unique properties of each cell lines. Results obtained from this study imply that diverse mechanisms are employed in D2NGC infection in different cells. This information will contribute towards further understanding of the mechanisms of DEN virus infection.